Reagent-Free Esterification from Benzoyl Hydrazines and Alcohols under Electrochemical Conditions - Xie, Peixu; Peng, Xichao; Feng, Pengju (Synthesis, 2023)
A scalable electrochemical esterification between aroylhydrazides and alcohols to give structurally versatile carboxylic esters was developed. This strategy features mild reaction conditions and a relatively broad substrate scope with good functional group compatibility. In addition, the transformation is operationally simple and free from external oxidants and mediating chemical reagents.
Keywords: electrochemical synthesis; esterification; aroylhydrazides; reagent-free reaction; anode oxidation